2021
DOI: 10.1093/femsle/fnab111
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of lipid-accumulation of oleaginous yeast Rhodosporidium toruloides through CRISPR/Cas9-mediated inactivation of lipid droplet structural proteins

Abstract: The basidiomycetous yeast Rhodosporidium toruloides is an important chassis organism for producing microbial lipids and terpenoids. However, excess carbon flux flows towards lipid synthesis than terpenoid synthesis. Thus, it is essential to limit lipid accumulation so that R. toruloides can be explored as an advanced cell factory for producing non-lipid derivatives. In this study, we knocked out two lipid droplet (LD) structural proteins (Ldp1 and Cals) of R. toruloides NP11 through the CRISPR/Cas9 system to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a recent work, lipid accumulation was reduced through CRISPR/Cas9-mediated inactivation of lipid droplet structural proteins (Ldp1 and Cals). 107 Compared to the control that gave a lipid content at approximate 53%, the double-deletion mutant only showed a lipid content at approximate 25%. This significant decrease in lipid content suggested that the structural proteins (Ldp1 and Cals) had a positive impact on lipid production.…”
Section: Characterization and Mining Of Promotersmentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent work, lipid accumulation was reduced through CRISPR/Cas9-mediated inactivation of lipid droplet structural proteins (Ldp1 and Cals). 107 Compared to the control that gave a lipid content at approximate 53%, the double-deletion mutant only showed a lipid content at approximate 25%. This significant decrease in lipid content suggested that the structural proteins (Ldp1 and Cals) had a positive impact on lipid production.…”
Section: Characterization and Mining Of Promotersmentioning
confidence: 93%
“…This work has exhibited the highest efficiency of single knockout and double knockout to date. In a recent work, lipid accumulation was reduced through CRISPR/Cas9-mediated inactivation of lipid droplet structural proteins (Ldp1 and Cals) . Compared to the control that gave a lipid content at approximate 53%, the double-deletion mutant only showed a lipid content at approximate 25%.…”
Section: Development Of Synthetic Biology Elements and Toolsmentioning
confidence: 99%
“…Conventional strategies are often used in R. toruloides engineering, like overexpression of rate-limiting enzymes and increase in the copy number of terpenoid synthase genes (Geiselman et al, 2020;Liu et al, 2021a). In our previous investigation, a reduction of lipid accumulation was observed with the inactivation of lipid droplet structural proteins in R. toruloides, while the production of carotenoids was improved (Jiao et al, 2021). Particularly, the knockout of the perilipin gene LDP1 led to a 13% decrease in lipid content and a 93% increase in carotenoid content.…”
Section: Introductionmentioning
confidence: 93%
“…In the module of competing pathway disruption, the lipid droplet structural protein, namely, perilipin (Ldp1, GenBank ID: RHTO_05627), was inactivated by the CRISPR/Cas9 system. This strategy was based on our previous study, which suggested a reduction of lipid accumulation and higher production of carotenoids via knocking out the LDP1 gene (Jiao et al, 2021). The sgRNAs of two targeted genes (CRT and LDP1) were constructed according to the protocol mentioned in Jiao et al (2019).…”
Section: Re-casting the α-Terpineol Biosynthesis By R Toruloides Into...mentioning
confidence: 99%